Efektivitas Drainase Vertikal sebagai Mitigasi Likuefaksi dalam Ragam Potensi Percepatan Tanah Maksimum - Chariznantya Renatra; Widjojo Adi Prakoso (Jurnal Teknik Sipil, 2025)
Abstract Lolu Village, located in the Palu Koro fault groove and has a stratification of soil sediment that is layered with heterogeneous characters. Between the cohesive and granular soils, forming an overlapping layer. Lolu Village has its own challenges in dealing with the potential for earthquakes and liquefaction as a result. One of the liquefaction mitigations in SNI 8460:2017 is stone columns (SC) as a vertical drainage medium that functions to accelerate the rate of pore water dissipation. However, the condition of the layered soil interspersed with cohesive soil with low permeability, presents its own challenges in determining the depth of stone columns. It is necessary to review the extent of the effectiveness of SC against Peak Ground Accelerations (PGA) that have the potential to occur in Lolu Village. The stratification of the soil and stone columns will be modelled using the Midas GTS NX. Soil layers with liquefaction potential use the UBC Sand model and SC with the Mohr Coulomb model. When the stratification modeling of the soil was shaken by cyclic loads, it was found that only the upper granular layer was liquefaction. This identifies that the thin layer of cohesive soil between the layers of granular, has a role as a shield to resist the pore water pressure of the granular soil layer underneath. The study compared the initial soil conditions against two variations in the depth of SC. It was found that the depth of the SC was passed through the thin layer of cohesive soil between the granular layers, worsening the liquefaction condition of the upper layer. Keywords : Liquefaction, Midas GTS NX, Pore Pressure Ratio PPR, stone columns